FlywheelTools: Data Curation and Manipulation on the Flywheel Platform - Tapera, Tinashe M.; Cieslak, Matthew; Bertolero, Max; Adebimpe, Azeez; Aguirre, Geoffrey K.; Butler, Ellyn R.; Cook, Philip A.; Davila, Diego; Elliott, Mark A.; Linguiti, Sophia; Murtha, Kristin; Tackett, William; et al. (Frontiers in Neuroinformatics, 2021)
The recent and growing focus on reproducibility in neuroimaging studies has led many major academic centers to use cloud-based imaging databases for storing, analyzing, and sharing complex imaging data. Flywheel is one such database platform that offers easily accessible, large-scale data management, along with a framework for reproducible analyses through containerized pipelines. The Brain Imaging Data Structure (BIDS) is the de facto standard for neuroimaging data, but curating neuroimaging data into BIDS can be a challenging and time-consuming task. In particular, standard solutions for BIDS curation are limited on Flywheel. To address these challenges, we developed “FlywheelTools”, a software toolbox for reproducible data curation and manipulation on Flywheel. FlywheelTools includes two elements: fw-heudiconv, for heuristic-driven curation of data into BIDS, and flaudit, which audits and inventories projects on Flywheel. Together, these tools accelerate reproducible neuroscience research on the widely used Flywheel platform.